COUNSELLING FOR CORRUPTION FREE EDUCATION SYSTEM: A SINE QUA NON FOR ELIMINATING CORRUPTION IN NIGERIAN SOCIAL SYSTEM - Ohuakanwa, Chijioke E. (African Journal of Social and Behavioural Sciences, 2021)
This paper tried to examine counselling for corruption-free education system: a sine qua non for eliminating corruption in Nigerian social system. The author in this paper is of the argument that effective counselling when sustained in the education system could be a means of eliminating education-based corruption and by extension eradicating corruption in the larger Nigeria social system. It is widely believed that no country the world over attains sustainable development in the face of corruption. It is worrisome, that corruption is subtly killing not only the education sector but also the nation generally. Education, as it were, has always been the instrument of change. In the case of corruption, it could be a veritable weapon of curbing corruption in Nigeria, but unfortunately, it is a terrible challenge that education sector itself is one of the worst victims of the virus of corruption. A whole lot of brands of corruption ravage the education sector (the school system and its allies). This is very sad, in the sense that if the engine room of the healing block is infected by the disease, then there is catastrophe at hand. Any kinds of corruption in the education sector will surely rub off on the entire sectors of the country’s economy. It could be examination fraud or malpractice among Nigerian students; it could be academic fraud among tertiary institution workers (academic and non-academic) it could be education administrative fraud that ravage the bodies responsible for managing the education sector and so on. In this paper therefore, counselling for corruption free education system, in the view of the author is believed to be a sine qua non for eliminating corruption in Nigerian education sector and by extension the Nigerian social system. Thus, it is recommended in this paper that there should be a holistic reassessment of the introduction of counselling services in Nigerian schools with the intent to enhance the implementation of the programme at all levels of the educational system in Nigeria,bearing in mind its relevance.